THE ROLE OF DIGITAL PLATFORM AND AI TOOLS IN THE DEVELOPMENT OF ORAL SPEECH OF SCHOOL STUDENTS - Ghiysiddinov Ayubkhan Akmalivych, Kodirov Alijon Abdumannonovich (International Journal of Literature and Language Studies, 2026)
This article scientifically analyzes the pedagogical potential of digital platforms and artificial intelligence (AI) tools in developing oral speech competence of schoolchildren. In the modern education system, an educational environment organized on the basis of digital pedagogy serves to develop students' communicative competence, form independent thinking skills, and improve their ability to communicate freely in a foreign language. During the study, the linguodidactic potential of AI technologies in teaching English, the effectiveness of interactive platforms, and innovative methods in developing oral speech were studied. The results of the study showed that the use of digital platforms and AI tools significantly increases students' speech activity, pronunciation, vocabulary, and communicative competence.